Konsep Boikot dalam Al-Qur’an: Studi atas Kitab Tafsīr Sūrah Al-Mumtaḥanah Karya ‘Alī Khāmenei - Ali Falaqul Ishbah; Muhammad Babul Ulum; Dani Nur Pajar (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
The recent phenomenon of boycotts has attracted global attention. There have been both pros and cons in viewing the boycott movement. Some believe that this movement causes loss to certain parties, while others argue that boycotts are a necessary choice to exert pressure on groups that threaten the existence of others. Against this background, this sresearch aims to resolve the intellectual dispute in society and provide a scholarly response by examining the movement from the perspective of the Qur’an. The author uses the perspective of ‘Alī Khāmenei and his work, “Tafsīr Sūrah Al-Mumtaḥanah”. This research is a thematic-figure study using a qualitative method based on literature sources. The study concludes that ‘Alī Khāmenei views the boycott as a declaration of ‘barā’ah’ (disassociation) from the enemies of Allah and Islam. According to Khāmenei’s view, the boycott must cover three aspects: separation of the heart, ideology, and practice. This was exemplified by Prophet Ibrahim (AS) and is mentioned in Surat Al-Mumtaḥanah. Those who should be boycotted are those who deny the truth of Islam and who expel or wage war against Muslims. One group that openly engages in such actions is the Israel Zionism. ‘Alī Khāmenei encourages Muslims to take preventive action by boycotting them. The boycott serves as a way to prevent Muslims from being considered traitors while maintaining their faith, which could harm Islam by forming ties with infidels. A practical form of the boycott, for example, includes not establishing cooperation with Zionist Israel or those who support them, not purchasing their products, and avoiding any kind of affiliation with them.